Maternal exposure to ambient ozone and congenital diaphragmatic hernia: A population-based retrospective cohort study from Florida, 1998–2012. (15th November 2022) - Ramakrishnan, Rema; Stuart, Amy L.; Salemi, Jason L.; Chen, Henian; O'Rourke, Kathleen; Kirby, Russell S.
Abstract: Background: Congenital diaphragmatic hernia (CDH) is a rare birth defect with a global prevalence of 2.3 per 10, 000 (range: 1.1–8.0 per 10, 000). Ambient ozone has been associated with several birth defects; however, there is limited evidence for its role in the etiology of CDH. We examined the role of maternal exposure to ambient ozone as a risk factor for CDH (overall and stratified by isolated and complex) in the State of Florida. Methods: We conducted a population-based, retrospective cohort study using data from the 1998–2012 Florida Birth Defects Registry and the Environmental Protection Agency's Air Quality System. Maternal exposure was estimated by combining data to determine ozone concentrations during pregnancy for maternal census tract (at delivery) using a space-time inverse distance squared weighting method. Multilevel Poisson regression models were used to calculate the risk of CDH, overall and stratified by isolated and complex. Results: The study population consisted of 2, 649, 846 singleton live births including 814 cases of CDH. The findings indicate insufficient evidence for an association between maternal exposure to ambient ozone and CDH during the etiologically relevant time window for CDH (4–12 weeks of pregnancy). Prevalence ratios and 95% confidence intervals for each increasing quartile of ozone exposure level relative to the lowest quartile were: for overall CDH: 1.12 (0.92, 1.36), 0.99 (0.81, 1.22), and 1.12 (0.94, 1.40); for isolated CDH: 1.08 (0.86, 1.36), 1.01 (0.80, 1.28), and 1.15 (0.92, 1.44); and for complex CDH: 1.22 (0.91, 1.63), 0.92 (0.67, 1.25), and 1.12 (0.83, 1.52). Conclusions: Our results do not support a link between maternal exposure to ambient ozone and CDH. Studies with better exposure assessment and inclusion of spontaneous and planned abortions may be needed. Gene-environment interactions and the study of maternal vitamin A status as a mediator in the pathway between ambient ozone and CDH may provide further information on the potential role of ambient ozone in the etiology of CDH. Graphical abstract: Image 1 Highlights: The link between ozone exposure and congenital diaphragmatic hernia was studied. The study included 2, 649, 846 singleton infants born alive in 1998–2012 in Florida. The prevalence ratio for CDH with increasing ozone exposure level was inconsistent. The 4th exposure quartile had the highest prevalence ratio for isolated CDH. Evidence was insufficient for association between ozone and CDH.